Elevated Circulating IL-1 β and TNF-Alpha, and Unaltered IL-6 in First-Trimester Pregnancies Complicated by Threatened Abortion With an Adverse Outcome (Mediators of Inflammation)
The purpose of the present study was to examine the profile of selected proinflammatory cytokines in maternal serum of first-trimester pregnancies complicated by threatened abortion (TACP) and its relevance to obstetric outcome. Serum levels of Th1-type cytokines interleukin-1 β (IL-1 β ), tumor necrosis factor alpha (TNF-alpha), and Th2-type cytokine interleukin 6 (IL-6) were measured, by ELISA, in 22 women with TACP and adverse outcome at admission (group A) and compared with the corresponding levels of 31 gestational age-matched women with TACP and successful outcome at admission (group B1) and discharge (group B2) and 22 gestational age-matched women with first-trimester uncomplicated pregnancy (group C) who served as controls. Mann-Whitney U or Wilcoxon test was applied as appropriate to compare differences between groups. IL-1 β and TNF-alpha were detected with significantly higher levels in group A, compared to all other groups. On the contrary, IL-6 levels were detected with no significant difference among all the other groups studied. It is concluded that in first-trimester TACP with adverse outcome, a distinct immune response, as reflected by elevated maternal IL-1 β , TNF-alpha, and unaltered IL-6 levels, is relevant to a negative obstetric outcome.